A caracterização do assédio moral no sistema penitenciário: uma análise das manifestações de assédio moral no âmbito da Secretaria de Administração Prisional do Estado de Minas Gerais - Rodrigo Xavier da Silva (2017)
The present study aimed to broaden the discussion and visibility of the phenomenon of harassment among workers in the Penitentiary System of Minas Gerais. The research also aimed to identify and understand how these harassing practices are characterized, based on the analysis of content of denunciations formally registered in the Directorate of Human Resources of the State Secretariat of Prison Administration of the State of Minas Gerais, in the years of 2015- 2016. This is a qualitative study, with a focus based on the theoretical assumptions of Marie-France Hirigoyen and the psychodynamics of work, by Christophe Dejours. The methodological procedures adopted were bibliographic and documentary research. Data analysis was based on the content analysis of Bardin (1977). This work has also proposed to highlight the circumstances and feelings that favor the practice of bullying. In his conclusion, he records that bullying manifests itself, in general, through repeated disqualification, in situations of vertical hierarchy, through the deliberate deterioration of working conditions. It also records the weaknesses found in state legislation, which does not cover all factual situations that characterize moral violence in the public service. The study also suggests suggestions for the improvement of a policy of prevention and accountability of the practice of bullying in the scope of the Prison System of Minas Gerais.